The Feasibility of Assessing Perfusion of the Bone Using Quantitative ICG Fluorescence Imaging - Boldewijn, Danielle; Michi, Marlies; Smit, Jan Maerten; Joosten, Hanneke; Bruin, Daniel de; Elzen, Richard van den; Driessen, Caroline (Journal of Reconstructive Microsurgery Open, 2024)
Background  Near-infrared fluorescence (NIRF) imaging using indocyanine green (ICG) allows perfusion to be visualized and objective perfusion parameters can be provided after additional measurements. Therefore, it has great potential in predicting adequate tissue perfusion. However, regarding bone tissue, evidence of the feasibility and usefulness of NIRF imaging using ICG is very limited.Methods A prospective monocentric pilot study was carried out at a tertiary hospital in the Netherlands. Patients undergoing autologous breast reconstruction from August 2021 to August 2022 were included. During surgery, ICG (0.1 mg/kg) was injected intravenously and a fluorescent angiogram of 4 minutes was made directly after injection. Post hoc time-intensity curves were generated for a 5-mm region of interest (ROI) positioned on the cross-sectional lateral surface of the rib. The first moment of increase of intensity was defined as t0. Fluorescent parameters included ingress and egress of ICG.Results Nine patients and 11 ribs were included for further analysis. Time-intensity curves were generated for endosteal measurement in 10 ribs. Three of the curves showed a steep and well-defined ingress and egress. In all other patients, the curves showed a much more flattened ingress and egress. Periosteal measurement was performed in nine ribs. No adverse events related to the ICG injection were observed intraoperatively.Conclusion This feasibility study suggests that quantitative NIRF imaging using ICG can provide objective parameters of endosteal rib perfusion. Larger prospective series are needed to investigate the value of NIRF imaging using ICG to assess bone perfusion intraoperatively and to establish cutoff values for adequate bone perfusion.
Keywords: fluorescence imaging; ICG; bone perfusion